Prednisolone versus Prednisolone combined with Acyclovir for the Treatment of Bell's Palsy: A Comparative Study in Peripheral Referral Centre - Shrestha, Karuna; Shah, Rajeev; Sapkota, Srijana; Giri, Sandarva (Birat Journal of Health Sciences, 2018)
Introduction: Bell's palsy is an idiopathic facial nerve palsy of sudden onset, usually, unilateral. Recent evidence suggests association of Herpes simplex infection with Bell's palsy but exact cause is unknown. Prednisolone are widely used in the treatment of Bell's palsy. However, the efficacy of additional treatment with acyclovir is uncertain.Objective: To evaluate whether a prednisolone with acyclovir provide a better degree of facial muscle recovery outcomes than prednisolone alone in patient with Bell's palsy.Methodology: This is a hospital based longitudinal cross sectional study conducted in Birat Medical College and Teaching Hospital and Birat Hospital PVT LTD, Biratnagar, Nepal from January 2017 to May 2018. A total of 42 patient diagnosed with Bell's palsy are included in this study, where 21 patient are treated with prednisolone and remaining 21 patient treated with a combination of prednisolone and acyclovir. The House-Brackmann grading scale is used for recording the initial presentation of patient with Bell's palsy and their early recovery on follow-up visit. The collected data was analysed using SPSS 18.0.Results: The total number of patients included in this study was 42. Mean age of patients is 27.1±10 years. Among them 25 (59.5%) were male and 17(40.5%) were female where male and female ratio is 1.5:1. Prednisolone plus acyclovir given in combination in Bell's palsy patients has as 76.2% recovery while prednisolone given alone has a 57.1% recovery P value